Modification of the susceptibility gene TaPsIPK1 - a win-win for wheat disease resistance and yield - Alberto Macho; Pengcheng Wang; Jian-Kang Zhu (Stress Biology, 2022)
Abstract Wheat is one of the most important cereal crops, and it is essential for worldwide food security. However, wheat production is threatened by various diseases, including wheat stripe rust caused by the fungus Puccinia striiformis f. sp. tritici (Pst). The development of plant resistance against disease is usually challenged by potential reduction in crop yield due to the enhancement of plant immunity. In a recent article, Wang et al. found that TaPsIPK1 is a susceptibility gene targeted by rust effectors. Editing of TaPsIPK1 increases resistance to stripe rust without any developmental effects or yield penalty, providing an exceptional resource for developing disease resistance in wheat.